MENYELISIK HUKUM PERNIKAHAN BEDA AGAMA DALAM Al-QURAN - Nurinayah Bahry (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
Interfaith marriages, that often occur because of love, ignores the legal aspects, whereas marriage is not only about love, but is also related to law. This article discusses the interpretation of Al-Qur'an in Surah Al-Baqarah verse 221 and other related verses, regarding the law of interfaith marriage. This verse shows that religion does not allow Muslim women to marry non-Muslim men; polytheists and scribes. It is also illegal to marry a polytheist woman, whether it is a pagan, Buddhist, or atheist. As for the law of Muslim men marrying people of the book (Jews and Christians) who still adhere to the scripture, the fiqh experts are divided into two groups. The first group argues that Muslim men can marry people of the book. The second group argues that it is unlawful to marry people of the book.